2022
DOI: 10.3390/ma15072685
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dissolution and Modification of Cotton Fiber in Different Growth Stages

Abstract: Cotton fibers with ultra-high purity cellulose are ideal raw materials for producing nanocellulose. However, the strong hydrogen bond and high crystallinity of cotton fibers affect the dissociation of cotton fibers to prepare nanocellulose. The structures of two kinds of cotton fibers (CM and XM) in different growth stages from 10 to 50 days post-anthesis (dpa) were studied by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). In the process of cotton fiber growth, the deposition rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The cotton linter (CL) exhibited obvious diffraction peaks at 14.9°, 16.5°, 22.7°, and 34.4°, which indicated that the natural cotton fibers used in the experiment had the typical cellulose type I crystal structure. 45 The characteristic peaks of Fe 3 O 4 /CL were mostly coincident with CL, which was due to the low loading of Fe 3 O 4 on untreated CL and the limitations of XRD. Interestingly, only the characteristic peaks of cellulose could be observed for Fe 3 O 4 /CL-O, which may have been related to the high dispersion of Fe 3 O 4 on the surface of CL-O, and this phenomenon was confirmed by SEM ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The cotton linter (CL) exhibited obvious diffraction peaks at 14.9°, 16.5°, 22.7°, and 34.4°, which indicated that the natural cotton fibers used in the experiment had the typical cellulose type I crystal structure. 45 The characteristic peaks of Fe 3 O 4 /CL were mostly coincident with CL, which was due to the low loading of Fe 3 O 4 on untreated CL and the limitations of XRD. Interestingly, only the characteristic peaks of cellulose could be observed for Fe 3 O 4 /CL-O, which may have been related to the high dispersion of Fe 3 O 4 on the surface of CL-O, and this phenomenon was confirmed by SEM ( Fig.…”
Section: Resultsmentioning
confidence: 98%